Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Calon Mahasiswa Baru Untuk Tidak Melanjutkan Registrasi Pada Tahun 2022-2023 : Studi Kasus Pada Universitas Swasta di Bandung - Agung M. Taufik; M. Budi Djatmiko (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the factors that influence the decision of prospective new students not to continue the registration process at a private university in Bandung. This phenomenon often occurs in various higher education institutions and has an impact on student admission and retention strategies. Potential factors influencing the decision include tuition fees, university reputation, study program quality, administrative services, as well as external factors such as scholarship offers and career opportunities. This research uses a quantitative approach with a questionnaire survey method distributed through Google Forms. The research sample consisted of prospective students who had registered but did not proceed to the final registration stage. Data was collected using a questionnaire that measured various variables such as tuition fees, perceived program quality, campus facilities, and external influences, with a five-point Likert scale to determine the respondents' level of agreement with each factor. The results of this study found that inadequate accreditation was the main reason influencing the decision of prospective private university students not to continue their registration, with 49.8% of respondents citing this factor as the most influential. Other significant factors include lack of follow-up from the university (32.5%), poor campus location (27.6%), and tuition fees that are considered too high (23.2%). Meanwhile, the factor of unsatisfactory service has the lowest influence, only 7.4%. This finding indicates that aspects of accreditation, facilities, communication, and cost are important elements in prospective students' decision making to continue registration at a private university.